MEMBANGUN MINAT ANAK SEKOLAH MINGGU MELALUI PENDAMPINGAN MAHASISWA DALAM PENGAJARAN DAN PENGGUNAAN ALAT PERAGA PADA MATERI BANGUN DATAR DI GEDUNG PAR DOK IX TANJUNG RIA JAYAPURA - Lestari, Tri Kurniah; Mutmainnah, Nurul; Buchori, Ahmad; Ernawati, Ernawati (LPPM Universitas Bina Bangsa, 2024)
The purpose of this community service is to enhance children's knowledge and interest in learning outside of school activities. The learning process is a crucial step in achieving educational goals, with interaction and goal achievement as the focus. Structured planning and appropriate teaching methods are required, including learning resources and active interaction between educators and children. Learning media, especially instructional tools, play a vital role in facilitating the learning process, particularly in mathematics education such as plane geometry concepts. Teaching activities using plane geometry models are conducted in Sunday School to help children understand these concepts in hopes of enhancing effective and enjoyable learning. Through implementation involving model making, active teaching, and evaluation, it can be observed that the use of models positively influences children's level of understanding and interest in learning. Students' understanding level based on evaluation results is 77.33, and the interest survey results are at 3.751 or equivalent to 89%, indicating that children's interest in learning falls under the category of very good. Future recommendations include encouraging active participation of children, providing constructive feedback, collaborating with parents, and implementing engaging teaching approaches